Cost-effectiveness of treating relapsed or refractory 3L+ follicular lymphoma with axicabtagene ciloleucel vs mosunetuzumab in the United States - Oluwole, Olalekan O.; Ray, Markqayne D.; Zur, Richard M.; Ferrufino, Cheryl P.; Doble, Brett; Patel, Anik R.; Bilir, S. Pinar (Frontiers in Immunology, 2024)
Novel therapies for 3L+ relapsed/refractory (r/r) follicular lymphoma (FL) have been approved recently by the US Food and Drug Administration including anti-CD19 CAR-T therapies such as axicabtagene ciloleucel (axi-cel) and CD20 × CD3 T-cell-engaging bispecific monoclonal antibodies such as mosunetuzumab (mosun). The objective of this study was to assess the cost-effectiveness of axi-cel compared to mosun in 3L+ r/r FL patients from a US third-party payer perspective. A three-state (progression-free, progressed disease, death) partitioned-survival model was used to compare two treatments over a lifetime horizon in a hypothetical cohort of US adults (age ≥18) receiving 3L+ treatment for r/r FL. ZUMA-5 and GO29781 trial data were used to inform progression-free survival (PFS) and overall survival (OS). Mosun survival was modeled via hazard ratios (HRs) applied to axi-cel survival curves. The PFS HR value was estimated via a matching-adjusted indirect comparison (MAIC) based on mosun pseudo-individual patient data and adjusted axi-cel data to account for trial populations differences. One-way sensitivity analysis (OWSA) and probabilistic sensitivity analyses (PSA) were conducted. Scenario analyses included: 1) the mosun HRs were applied to the weighted (adjusted) ZUMA-5 24-month data to most exactly reflect the MAIC, 2) mosun HR values were applied to axi-cel 48-month follow-up data, and 3) recent axi-cel health state utility values in diffuse large B-cell lymphoma patients. The analysis estimated increases of 1.82 LY and 1.89 QALY for axi-cel compared to mosun. PFS for axi-cel patients was 6.42 LY vs. 1.60 LY for mosun. Increase of $257,113 in the progression-free state was driven by one-time axi-cel treatment costs. Total incremental costs for axi-cel were $204,377, resulting in an ICER of $108,307/QALY gained. The OWSA led to ICERs ranging from $240,255 to $75,624, with all but two parameters falling below $150,000/QALY. In the PSA, axi-cel had an 64% probability of being cost-effective across 5,000 iterations using a $150,000 willingness-to-pay threshold. Scenarios one and two resulted in ICERs of $105,353 and $102,695, respectively. This study finds that axi-cel is cost-effective compared to mosun at the commonly cited $150,000/QALY US willingness-to-pay threshold, with robust results across a range of sensitivity analyses accounting for parameter uncertainty.